Arteriovenous cerebral high-flow shunts: genetic analysis of patients from a pediatric tertiary care center - Romano, Ferruccio; De Marco, Patrizia; Amico, Giulia; Mallamaci, Marisa; Pavanello, Marco; Piatelli, Gianluca; Scala, Marcello; Zara, Federico; Faravelli, Francesca; Severino, Mariasavina; Tortora, Domenico; Pasetti, Francesco; et al. (Frontiers in Genetics, 2025)
IntroductionArteriovenous cerebral high-flow shunts include the vein of Galen aneurysmal malformation (VGAM) and vein of Galen dilatation, which are considered secondary to arteriovenous malformations or arteriovenous fistulas. These entities are often sporadic but are found in association with variants of the RASA1 and EPHB4 genes (capillary malformation–arteriovenous malformation, CMAVM; OMIM #608354) or ACVRL1, ENG, and SMAD4 genes (hereditary hemorrhagic telangiectasia, HHT; OMIM #187300). The clinical phenotypes associated with these conditions are highly variable, with incomplete penetrance and mostly dependent on the hemodynamic consequences (including heart failure and cerebral hemorrhage) or management complications rather than anatomical vascular variations per se. The present study aimed to genetically characterize a cohort of 29 patients affected by arteriovenous cerebral high-flow shunts who were treated at a pediatric referral center.MethodsThe genetic techniques employed include next-generation sequencing, multiplex ligation-dependent probe amplification, and whole-exome sequencing.ResultsOf the 29 patients, 11 cases were found to have variants in genes associated with vascular functions, five cases received a genetic diagnosis, one case presented with a variant of uncertain significance in the EPHB4 gene, and five cases showed variants in novel genes possibly linked with cerebrovascular disorders.DiscussionWe provide extensive case descriptions and attempt to infer the genotype–phenotype correlations; variants in all of the known genes associated with arteriovenous cerebral shunts were reported in VGAM patients, while cutaneous angiomas were specific to RASA1 mutations. The genotypic and phenotypic descriptions of the affected individuals may thus have relevant implications in terms of better pathophysiological understanding, genotype–phenotype correlations, treatment strategies, and outcomes.